Centers and peripheries: Spatial analysis of social inequalities in health in Antioquia, 2017–2023 - Gino Montenegro-Martínez (PLOS Global Public Health, 2026)
This study aims to analyze the performance and geographical distribution of health indicators in relation to social indicators in the municipalities of Antioquia. An ecological cross-sectional study was conducted using data on health outcomes, social indicators, and institutional capacity of the municipalities of the department for the period 2017–2023. The analysis was performed using global and local Moran’s I statistics in order to identify the spatial correlation between health and social indicators . The global analysis reported significant associations only for the infant mortality rate, which showed positive correlations with the Multidimensional Poverty Index (MPI), Unmet Basic Needs (UBN), and Armed Conflict Index (ACI), and a negative correlation with the Municipal Performance Index (MPIn). The local analysis revealed correlations between poorer health and social indicators concentrated mainly in municipalities in the northern of the department, including the subregions of Bajo Cauca, Urabá, and Norte, while better conditions were found in municipalities of the Valle de Aburrá and parts of eastern Antioquia. Significant health inequalities persist in Antioquia, closely linked to poverty, armed conflict, and institutional limitations. The identified spatial patterns confirm a center–periphery dynamic, highlighting the need for planning approaches that are more sensitive to territorial diversity and local trajectories.